THE USE OF DIGITAL ANIMATED STORIES TO IMPROVE STUDENT’S LISTENING SKILL - Selvia Nurul; Aulia Hanifah Qomar; Fitri Palupi Kusumawati (English Education Study Program, 2025)
Listening is the process of receiving, interpreting, and understanding auditory stimuli, usually in the form of spoken words and other sounds. This research aims to determine the effect of digital animated stories in improving student's listening skills and to determine students' perceptions of the use of digital animated stories. The design of this research is Classroom Action Research. The procedure of Classroom Action Research is planning, action, observation, and reflection. This research was conducted at eleventh grade at SMK AL-FAJAR consist of 31 students. The results of this research indicate that digital animated stories significantly improve students' listening skills, with average test scores increasing from 47.09 in the pre-test to 59.1 after Cycle 1. This shows an increase of 25.5 compared to the pre-test score, and then to 77.9 in Cycle 2. The investigation into students' perceptions of digital animated stories showed that students had positive perceptions of digital animated stories, reporting increased engagement, motivation and comprehension. The integration of these stories also improved the classroom environment, encouraging greater focus and participation, aligning with existing research on the benefits of digital animated stories in language learning. In conclusion, this research provides compelling evidence that digital animated stories are a highly effective tool for enhancing students' listening skills, shaping positive perceptions of learning materials, and improving classroom dynamics. The findings suggest that digital animated stories can be an effective tool in enhancing listening skills in an EFL context. This study recommends the integration of digital animated stories into the regular curriculum to support language learning and improve student outcomes.